The Relationship between Real Earnings Management and Cost Behavior - Boakye, Bismark Yiadom; Atiso, Francis; Koranteng, Elvis (SEISENSE (PRIVATE) LIMITED, 2019)
Purpose- This research aims to examine the relationship between real earnings management (REM) and sticky Selling General and Administrative (SG&A) costs in the case of a developing economy. Design/Methodology- The study employed a purposive sampling method. Fifteen firms listed on Ghana stock exchange were selected for the study. Data from the period of 2005 to 20014 were collected. Findings- The study finds Ghanaian listed firm's SG&A cost to be sticky and also see these firms to manipulate earnings through REM. This study finds that REM through discretionary expenses and production cost increases sticky SG&A cost, whereas REM through cash flow reduces sticky SG&A cost. Overall, the results imply that REM exhibit sticky cost. Practical Implications- The study informs managers that cost is not only fixed or variable but also behaves asymmetrically. The understanding of this concept could help managers to implement strategies that will lower the cost of doing business. Also, since some managers deliberately make decisions that lead to real earnings management and sticky cost, we, therefore, believe that this research will be of importance to regulatory bodies, policymakers, investors, and other stakeholders.